The Effect of Force-Feeding, Fasting and Glucose Saturated Water Intake on the Contents of Some Biochemical Parameters in Plasma of Peking Ducks - Zhang, C.L.; Niu, Z.Y.; Hou, S.S.; Liu, F.Z.; Huang, W.; Xie, M. (International Journal of Poultry Science, 2005)
This experiment was conducted to evaluate the accuracy of a bioassay method for metabolizable energy for domestic duck, which was previously developed by our research group. 110 adult Peking drakes with similar weight were randomly allotted to 2 groups in each of 55 birds, one was treatment group and another was control group. Prior to trial, all birds were fasted for 12h, but water were provided ad libitum. And 5 birds from each group were web-bled from their venous in wings. At the same time, each bird of the tow groups was force-fed by pelleted feed 50g, then they were fasted but water was provided ad libitum. 4h later, drakes of the trial group were intake glucose saturated solution once every 6h for 15 minutes. At 2h, 12h, 24h, 36h, 48h after force-feeding, ten birds from each group were web-bled and discarded, respectively. Contents of glucose, uric acid, total protein, triglyceride, insulin, triiodothyronine, corticosteroid in plasma were measured. The results indicated that contents of glucose, uric acid and total protein in plasma didn`t fluctuate during the starvation of 48h. However, the content of triiodothyronine in plasma tended to decline, but it showed nonsignificant (p>0.05). Therefore, those drakes weren`t in abnormal conditions. Feeding glucose saturated solution to fasted drakes could alleviate the decrease of triiodothyronine in plasma. Fast resulted in the decease of insulin content in plasma. The plasma insulin content of fasted drakes fed glucose saturated solution is steady. Force feeding and fast didn`t cause the change of the corticosteroid content in plasma, which indicated that forementioned treatments didn`t make ducks under stress.